Early and midterm results of endovascular repair of abdominal aortic aneurysms with Anaconda stent graft - Ugur Gocen; Atakan Atalay (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2016)
Purpose: In this study, we aim to report our early and midterm results of endovascular replacement of abdominal aortic aneurysms with Anaconda stent graft. Material and Methods: Between January 2014 and June 2016, a total number of 32 patients who underwent endovascular aortic replacement (EVAR) with Anaconda stent graft electively or emergently were retrospectively analysed. Twenty-nine patients undergoing elective, 2 patients were processed as urgent. Average follow-up was 16.3 months (range, 1-28 months). Mortality, morbidity, survival rates, mean duration of operation, mean length of intensive care unit and hospital stays, the type and incidence of endoleaks, contrast nephropathy rates, the impact on leakage of the aortic diameter, complication rates and secondary intervention rates were recorded. Results: Early term hospital follow-up no mortality was observed, mortality was observed in one patient due to myocardial infarction one and a half months later. A leg thrombosis of stent occurred in two patients. Embolectomy was performed for one patient, ilio-ileal bypass applied for the other patients. Short-term results in terms of patient satisfaction with endovascular repair of aortic stent grafts anaconda and shows that good in terms of results. Conclusion: Endovascular aortic replacement (EVAR) can be selected as a treatment option in abdominal aortic aneurysm patients with co-morbidities and high mortality risk. We have received successful results in early and midterm results in our patients with abdominal aortic aneurysm endovascular treatment with Anaconda stent graft. [Cukurova Med J 2016; 41(4.000): 754-761]